Effect of Precursor Concentration and Annealed Substrate Temperature on the Crystal Structure, Electronic and Optical Properties of ZnO thin film - Yus Rama Denny Muchtar; Teguh Firmansyah; Adhitya Trenggono; Danu Wijaya; Ganesha Antarnusa; Andri Suherman (The Journal of Pure and Applied Chemistry Research, 2020)
This study carried out on the effect of precursor concentration and annealed substrate temperature on the crystal structure, electronic and optical properties of ZnO thin film. An aqueous solution of Acid Nitrite was used as precursors and its concentration was varied from 0.1 M to 0.4 M. The ZnO thin film was deposited on the glass substrate by Spray Pyrolysis Deposition and annealed with different temperature from 300 oC to 600 oC. The crystal structure, electronic and optical properties were investigated by Scanning Electron Microscopy (SEM), X-ray diffraction (XRD) and UV-Spectrometer. XRD result showed that all thin films have amorphous hexagonal wurtzite crystalline. Particle sizes ranging from 21.83 to 43.67 nm were calculated through Debye-Scherer Method. It showed that the concentration of the precursor had slightly impact on the particle size. Meanwhile, the increase in particle size with increasing annealed temperature is found to be gradual. The average transparent of all thin film was more than 80%. The bandgap of the ZnO thin films was estimated by Tauc Plot Relation. It showed that the bandgap values were increased with the increasing of precursor concentration due to Burstein-Moss Effect. In addition, the decrease in band gap values was found with increasing annealed temperature. Our results demonstrated that the varying precursor concentration and annealed substrate temperature can enhance the structure, electronic and the optical properties of ZnO thin films.